Analisis Pengaruh Laba Bersih, Arus Kas Operasi, Dan Debt To Equity (DER) Terhadap Return Saham Pada Perusahaan Manufaktur Sub Sektor Pengelola Sawit Crude Palm Oil (CPO) Yangterdaftar Di Bursa Efek Indonesia (BEI) Periode 2017- 2022 - Tilam Sari, Titis; Yuliati, Ika; Prihartanto, Andung (Accounting Research and Business Journal, 2024)
This research aims to determine the influence of Net Profit, Operating Cash Flow, Debt to Equity Ratio (DER) on Stock Returns, in manufacturing companies in the Crude Palm Oil palm oil sub-sector listed on the Indonesia Stock Exchange (BEI) in the 2017 - 2022 period. The sample uses purposive sampling with predetermined criteria. Based on these criteria, a sample of 5 companies was obtained during 6 years of observation. The data used is secondary data. To find out whether the processed data is appropriate or not, researchers use the classic assumption test. The analysis technique used is the multiple linear regression test technique and hypothesis testing using the t test, F test with a significance level of 5% and coefficient of determination. The results of the partial test calculation for the Net Profit variable obtained a significant level of 0.390> 0.05 so it can be interpreted as having no effect. The results of the partial test calculation for the Operating Cash Flow variable obtained a significant level of 0.032 < 0.05 so it is interpreted as having an effect. The results of the partial test calculation for the Debt to Equity Ratio variable have a significant level of 0.815 > 0.05 so it can be interpreted as having no effect. The research results show that f count > f table (2.171 < 2.98) with a significance of 0.116 > 0.05 so it can be concluded that there is no simultaneous significant influence between the variables Net Profit (LB), Operating Cash Flow (AKO) and Debt to Equity Ratio (DER) to Return on Shares listed on the Indonesia Stock Exchange for the period 2017 - 2022.